PROTO- ARTHOPODS DIVERSITY, ESSENTIAL FOR UNDERSTANDING - VINEET KUMAR PODDAR (International Journal of Multidisciplinary Research and Studies, 2020)
Arthropods constitute a central and colossal component of Earth’s biosphere, at both the macroscopic and microscopic levels. Since the beginning of the Phanerozoic, these hyperdiverse, articulated animals have shaped most terrestrial and marine ecosystems, and their pivotal roles in trophic networks often have a direct and considerable impact on our industries and economy—be it vital or detrimental. The war on insects, prominently, waged in the name of a wasteful and profit-driven agriculture, has led to catastrophic consequences for the survivability of these animals worldwide, and the loss of pollinators to cascading ecosystem breakdowns . The agroeconomical peril to arthropods, in conjunction with other environmental crises caused by unbridled resource exploitation and consumption, such as global warming, threatens to irremediably pauperize the planet’s landscapes This waning and fragility stand in stark contrast to more than half-a-billion years of exceptional resilience to mass extinctions. Although trilobites, vanishing at the end of the Permian, are a notable exception, the body plans (which can be broadly defined based on morphoanatomy, see e.g. Aria of all other four largest and traditional arthropod groups—chelicerates, myriapods, “crustaceans” and insects—, all present by at least by the Late Devonian, diversified through all of the five major preAnthropocene biodiversity crises. Likely since the Jurassic insects have become by a large margin the most diversified and abundant of arthropods but all main lineages have characteristically experienced explosive radiations and have shown extended stability of their families and genera.